2002
DOI: 10.1021/la0156107
|View full text |Cite
|
Sign up to set email alerts
|

Dispersion and Stability Studies of Resorcinarene-Encapsulated Gold Nanoparticles

Abstract: Two resorcinarene surfactants with sulfur-functionalized headgroups have been evaluated for their ability to stabilize dispersions of midnanometer (16−87 nm)-sized gold particles in organic solvents. Citrate-stabilized colloidal gold nanoparticles were extracted from aqueous solutions into toluene or chloroform by tetrabenzylthiol resorcinarene 1 or tetraarylthiol resorcinarene 2. The nanoparticle dispersions were subjected to various conditions and monitored for changes in plasmon absorption intensity. The st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
98
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(102 citation statements)
references
References 47 publications
4
98
0
Order By: Relevance
“…38,39 Moreover, resorcinarene tetrathiols 6 and especially 7 were capable of extracting colloidal Au nanoparticles from aqueous solutions. { These classic 'Faraday sols' are easily produced in the 10-100 nm size range with narrow size distributions and are endowed with size-dependent optical properties, but their organization into well-defined ensembles had never been systematically addressed because of difficulties in dispersion control.…”
Section: Encapsulation Of Gold Nanoparticlesmentioning
confidence: 99%
See 2 more Smart Citations
“…38,39 Moreover, resorcinarene tetrathiols 6 and especially 7 were capable of extracting colloidal Au nanoparticles from aqueous solutions. { These classic 'Faraday sols' are easily produced in the 10-100 nm size range with narrow size distributions and are endowed with size-dependent optical properties, but their organization into well-defined ensembles had never been systematically addressed because of difficulties in dispersion control.…”
Section: Encapsulation Of Gold Nanoparticlesmentioning
confidence: 99%
“…Colloidal Au particles as large as 87 nm could be dispersed in chloroform-THF mixtures by tetrabenzylthiol resorcinarene 7. 39 The stability of the nanoparticles encapsulated by tetrathiols 6 and 7 was also evaluated against alkanethiolinduced precipitation in organic solvents. Both systems were far more stable than the nanocrystals coated with resorcinarenes 1 or 2, but 7 was significantly more robust in its chemisorption than 6 and could maintain a long dispersion half-life (t 1/2 y1 month) in the presence of alkanethiols at ambient temperature (see Fig.…”
Section: Encapsulation Of Gold Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, various bottom-up approaches, such as UV irradiation [6,7,15], chemical [3][4][5][6], thermochemical [3,6], sonochemical [3,6], and electrochemical reduction [16], have been reported for the synthesis of stable Au NPs of controlled shapes and sizes. Gold NPs of various structural architectures (e.g., rods, plates, disks, cubes, spheres, and stars) can be synthesized by proper manipulation of experimental parameters in the presence of surface-capping agents in the form of surfactants [3,17], polymers [3][4][5][6][7], and dendrimers [3,6]. However, among the various encapsulating agents, a macroscopic ligand especially a hydrophilic polymer like poly(vinylpyrrolidone) (PVP) is widely used in the synthesis of NMNPs [4][5][6]18,19].…”
Section: Introductionmentioning
confidence: 99%
“…The formation of GNPs in a non-hydrocolloid was confirmed by UVvisible, X-ray photoemission spectroscopy (XPS), and transmission electron microscope (TEM). An organic solvent was chosen in this work because such medium founds to provide low interfacial energies needed for a high degree of control during solution and surface processing is required for synthesis of nano colloids (Balasubramaniam et al 2002). Also it was reported that Au-NPs synthesized in an organic medium offer excellent control over size and possess superior processability (Sugunan et al 2005).…”
Section: Introductionmentioning
confidence: 99%